Development, growth and metabolic effects in stage IV lobster (Homarus americanus) following chronic exposure to sediments spiked with commercial formulations of deltamethrin and permethrin - Daoud, Dounia; Greenwood, Spencer J.; de Jourdan, Benjamin; Asnicar, Davide; Taylor, Laura J. (Frontiers in Physiology, 2023)
Coastal and estuarine ecosystems are environments heavily influenced by natural and anthropogenic activities. Chemicals used for pest control in agriculture and aquaculture may accumulate in natural coastal environments. Pyrethroids are common pesticides that are used on crops as well as applied to aquaculture pens and then may disperse in the surrounding ocean once treatment is complete. This study observed the sublethal effects of two pyrethroids, permethrin and deltamethrin (within commercially available formulations), on post-larval stage IV American lobster (Homarus americanus) using growth parameters and metabolic rate as indicators. Observed effects on growth parameters were a decrease in size increment and specific growth rate as well as an increase in intermolt period in stage IV lobsters exposed to 100 µg/kg permethrin. No significant differences were found for intermolt period, size increment, or specific growth rate in deltamethrin-exposed stage IV lobsters. Metabolic rates were not significantly different between deltamethrin-exposed and control lobsters, however, this sublethal effect warrants further investigation. Collectively, these results represent the first examination of the sublethal effects of exposure to pyrethroids formulations in post-larval lobsters, highlighting the potential for effects on non-target marine organisms.